ПОМОГИТЕ ООООЧЕНЬ НАДО!!!!
Ответы
Ответ:
В решении.
Объяснение:
4.1
а) 3х = 6
х = 6/3
х = 2;
б) х/3 = -5
х = -5 *3
х = -15;
в) -2х = 12
х = 12/-2
х = -6;
г) 3х/7 = 9
3х = 9 * 7
3х = 63
х = 63/3
х = 21.
4.2
а) 4х + 20 = 0
4х = -20
х = -20/4
х = -5;
б) 2х/3 - 6 = 0
2х/3 = 6
2х = 6 * 3
2х = 18
х = 18/2
х = 9;
в) 5х - 15 = 0
5х = 15
х = 15/5
х = 3;
г) 2х/5 + 4 = 0
2х/5 = -4
2х = -4 * 5
2х = -20
х = -10.
4.3
а) 7х + 9 = 100
7х = 100 - 9
7х = 91
х = 91/7
х = 13;
б) 26х - 0,8 = 7
26х = 7 + 0,8
26х = 7,8
х = 7,8/26
х = 0,3;
в) х/2 - 1/3 = 1/6
Умножить все части уравнения на 6, чтобы избавиться от дроби:
3х - 2 = 1
3х = 1 + 2
3х = 3
х = 1;
г) 17,5х - 0,5 = 34,5
17,5х = 34,5 + 0,5
17,5х = 35
х = 35/17,5
х = 2.
4.4
а) 9 + 13х = 35 + 26х
13х - 26х = 35 - 9
-13х = 26
х = 26/-13
х = -2;
б) 7х/9 + 3 = 2х/3 + 5
7х/9 - 2х/3 = 5 - 3
х/9 = 2
х = 2 * 9
х = 18;
в) 0,81х - 71 = 1,11х + 1
0,81х - 1,11х = 1 + 71
-0,3х = 72
х = 72/-0,3
х = -240;
г) у/3 - 4 = у/4 - 5
у/3 - у/4 = -5 + 4
х/12 = -1
х = -1 * 12
х = -12.
4.5
а) 11х - 4х = 14
7х = 14
х = 2;
б) 20х - 13х - 12х = 6
-5х = 6
х = 6/-5
х = -1,2;
в) 9х + 4х = -26
13х = -26
х = -2;
г) 11х + 7х - 24х = 42
-6х = 42
х = 42/-6
х = -7.
4.6
а) 5х/9 - 7х/4 + 17х/18 = -1/4
-9х/36 = -1/4
-х/4 = -1/4
х/4 = 1/4
х = 1/4 * 4
х = 1;
б) х/6 - 0,82 = 3х/8 - 1,37
х/6 - 3х/8 = -1,37 + 0,82
-5х/24 = -0,55
-5х = -0,55 * 24
-5х = -13,2
х = -13,2/-5
х = 2,64;
в) х/9 + 7х/18 - 11х/27 = 2 1/2
5х/54 = 5/2
5х = 5/2 * 54
5х = 135
х = 135/5
х = 27;
г) 0,07 - 3 1/9х = 0,26 - х
-3 1/9х + х = 0,26 - 0,07
-2 1/9х = 0,19
-19х/9 = 0,19
-19х = 0,19 * 9
-19х = 1,71
х = 1,71/-19
х = -0,09.
Все решения проверены, всё верно.